Development of an expert system prototype in identifying songket motif / Yazlinda Abdul Lath - Abdul Lath, Yazlinda (2003)
Songket Info System is an expert system which is computer-based system that can identify a songket motif image and name in automatically manner. This prototype system will be able to identify songket motif based upon user preferences. This prototype help user of the Textile students and lecturers identify motif of songket instantly. This project is available for the user with unknown data but have a pictorial input to gain information of the songket motif The objective of this project is to produce an expert system prototype that can identify songket motif as a medium of reference instead of using documented manual that take times in identifying. Besides that this project enables to identify information of songket motif in an efficient and systematically manner. The implementation of this project follows the process of the Prototype Lifecycle. Research is done through interviews with experts, observations, articles, Internet, books and journals. The information gained is analyzed and then the basic design of the prototype is drafted. Through continuous analysis and design, prototype architecture is developed. Later the coding phase is done with Borland C++ Builder. Testing is done at the end the coding phase to ensure the end prototype fulfill the objectives of the project and to sort out any errors or bugs in the system.